2021
DOI: 10.3390/land10121392
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Enriched with Buffalo Slurry Improved Soil Nitrogen and Carbon Dynamics, Nutrient Uptake and Growth Attributes of Wheat by Reducing Leaching Losses of Nutrients

Abstract: The present investigation was conducted to understand the role of enriched biochar on soil nitrogen and carbon dynamics, leaching losses of nutrients, and growth attributes of wheat. Buffalo slurry (BS) was used to enrich the biochar for 24 h and 2% biochar (SB) or enriched biochar (SEB) was used. Enrichment of biochar with BS as SEB improved the C and N contents of biochar by 33–310% and 41–286% respectively. The application of biochar (SB) and enriched biochar (SEB) reduced the net nitrification by 81% and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In our study, the average urease activities of CC treatment and CA treatment were 0.61 mg/g and 0.46 mg/g, respectively. The average urease activity of the high amount of biochar treatment was 10.67% higher than that of the control, consistent with previous research results [16,40]. Our outcomes are in line with other studies which found that biochar application increases urease activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the average urease activities of CC treatment and CA treatment were 0.61 mg/g and 0.46 mg/g, respectively. The average urease activity of the high amount of biochar treatment was 10.67% higher than that of the control, consistent with previous research results [16,40]. Our outcomes are in line with other studies which found that biochar application increases urease activity.…”
Section: Discussionsupporting
confidence: 93%
“…Biochar is a solid product derived from the pyrolysis of bio-organic materials (also known as biomass) in an anaerobic or hypoxic environment [14]. It has been noted that biochar has a large number of pores on its surface and has a strong adsorption capacity for water and gas, which is also conducive to the maintenance of nutrients such as N, P, and K [15,16]. Additionally, biochar addition can promote crop growth due to efficient utilization of nutrients in soil, the optimization of soil physical and chemical properties, and the reduction in heavy metal toxicity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Peat is organic waste and an economical carrier material that is rich in nutrients due to the presence of a variety of organic materials in its composition; these not only aid the growth and survival of bacteria but also provide crevices and microcolony particle surfaces for them [23,24,41]. Charcoal is considered to be a reservoir of carbon for soil and forests, which supports the survival of saprotrophic microorganisms and increases nutrient availability in the soil [42][43][44][45]. Based on the qualities of different carrier materials, it is imperative to test which carrier material has the maximum number of microbial populations with a positive impact on crop growth and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the total amount of soil elements was determined by mixed acid (HF-HNO 3 -HClO 4 ) ablation and inductively coupled plasma mass spectrometry, and the effective state content was determined via leaching and inductively coupled plasma emission spectrometry (HJ804-2006). Next, the N content in the leaves was determined using the H 2 SO 4 -H 2 O 2 ablation method, and the P content was determined using H 2 SO 4 -H 2 O 2 molybdenum gradient resistance colorimetry [22,23]. Subsequently, the K, Mn, Zn, Fe, Ca, and Mg contents were determined using inductively coupled plasma emission spectrometry (JD-02), the Cu content was determined using an iCAPQc plasma mass spectrometer (JD-03), and a one-meter planar grating spectrometer (JD-14) was used for B determination [24].…”
Section: Sample Analysismentioning
confidence: 99%